Anti-Melanogenic Activity of Gagunin D, a Highly Oxygenated Diterpenoid from the Marine Sponge Phorbas sp., via Modulating Tyrosinase Expression and Degradation - Ho Yeon Lee (Marine Drugs, 2016)
Tyrosinase is the rate-limiting enzyme critical for melanin synthesis and controls pigmentation in the skin. The inhibition of tyrosinase is currently the most common approach for the development of skin-whitening cosmetics. Gagunin D (GD), a highly oxygenated diterpenoid isolated from the marine sponge Phorbas sp., has exhibited cytotoxicity toward human leukemia cells. However, the effect of GD on normal cells and the molecular mechanisms remain to be elucidated. In the present study, we identified for the first time the anti-melanogenic activity of GD and its precise underlying mechanisms in mouse melan-a cells. GD significantly inhibited melanin synthesis in the melan-a cells and a reconstructed human skin model. Further analysis revealed that GD suppressed the expression of tyrosinase and increased the rate of tyrosinase degradation. GD also inhibited tyrosinase enzymatic activity. In addition, GD effectively suppressed the expression of proteins associated with melanosome transfer. These findings suggest that GD is a potential candidate for cosmetic formulations due to its multi-functional properties.